BRAF V600E mutation detection by immunohistochemistry in colorectal carcinoma. Issue 8 (7th May 2013) - Affolter, Kajsa; Samowitz, Wade; Tripp, Sheryl; Bronner, Mary P.
<x xml:space="preserve">Abstract</x> The serine/threonine‐protein kinase B‐raf (BRAF) is an oncogene mutated in various neoplasms, including 5–15% of colorectal carcinomas. The T1799A point mutation, responsible for a large majority of these alterations, results in an amino acid substitution (V600E) causing the constitutive activation of a protein kinase cascade. BRAF V600E in MLH1 deficient tumors implicates somatic tumor‐only methylation of the MLH1 promoter region instead of a germline MLH1 mutation. BRAF V600E also predicts poor prognosis in microsatellite stable colorectal cancers and may be a marker of resistance to anti‐EGFR therapy in metastatic disease. Currently, only molecular methods are available for assessing BRAF mutational status. An immunohistochemical approach is evaluated here. Colon cancers from 2008 to 2012 tested by pyrosequencing for BRAF V600E mutation were selected. A total of 31 tumors with (n = 14) and without (n = 17) the BRAF V600E mutation were analyzed by immunohistochemistry using a commercially available antibody specific to the V600E‐mutated protein. All 14 colorectal carcinomas with the BRAF V600E mutation demonstrated cytoplasmic positivity in tumor cells with the anti‐BRAF antibody. In a minority of cases, staining intensity for the mutated tumor samples was weak (n = 2) or heterogeneous (n = 4); however, the majority of cases showed diffuse, strong cytoplasmic positivity (8 of 14 cases). None of the 17 BRAF wild‐type colorectal cancers showed immunoreactivity to the antibody. The overall sensitivity and specificity of the immunohistochemical BRAF V600E assay was 100%. Detection of the BRAF V600E mutation in colorectal cancer by immunohistochemistry is a viable alternative to molecular methods. © 2013 Wiley Periodicals, Inc.